The Socialization of Waste Sorting and Management Action in RW 04 Jayawaras Village, Tarogong Kidul District, Garut Regency - Setiawan, Setiawan; Purnama, Dadang; Witdiawati, Witdiawati; Sunarya, Uu (LPPM STIKes Muhammadiyah Ciamis, 2024)
Waste is a material that is discarded or discarded from a source resulting from human activities or natural processes that has no economic value, and can even have a negative value because handling it, whether to dispose of it or clean it up, requires quite a large amount of money. Apart from that, the characteristic of waste is that it smells, waste can also cause infectious diseases such as tuberculosis, dengue fever, acute respiratory infections, diarrhea and other infectious diseases. A process of waste handling activities from the source by utilizing resources effectively starting from containerization, collection, transportation, processing to disposal through organizational management control that is environmentally friendly, namely waste sorting, to facilitate disposal and reprocessing, to separate organic waste disposal. , non-organic and B3 and to make waste environmentally friendly. Waste management or processing is an important part of waste handling to change waste into a form that is more stable and does not pollute the environment and reduces the amount of waste that must be deposited in TPA (Final Processing Place).